1960
DOI: 10.4319/lo.1960.5.4.0381
|View full text |Cite
|
Sign up to set email alerts
|

INTERTIDAL ZONATION IN POPULATIONS OF MYA ARENARIA1

Abstract: Observations over a 2-year period on the distribution of two succcssivc year-classes of Mya arennria in a tidal area near Quincy, Mass., indicated that young clams 2-15 mm in length were subject to appreciable changes in location in intertidal areas. Such changes involved a shorcward displacement of the mcmbcrs of the population as they excecclcd 5 mm in length, with a marked tendency for successive populations ultimately to bccomc concentrated near an abrupt change in the beach profile. The similarities bctwc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

1968
1968
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…3). Other species of clams (Donax hanleyanus, Mya arenaria) also preferentially settle in the swash zone, with increasing abundance patterns up the lowest low tide mark and a decrease into he subtidal, similar to our data (Matthiessen, 1960;Cardoso & Veloso, 2003). These clam species also display differences in their size distribution, with smaller individuals settling farther shoreward and larger individuals farther seaward (Matthiessen, 1960;Cardoso & Veloso, 2003).…”
Section: Discussionsupporting
confidence: 70%
“…3). Other species of clams (Donax hanleyanus, Mya arenaria) also preferentially settle in the swash zone, with increasing abundance patterns up the lowest low tide mark and a decrease into he subtidal, similar to our data (Matthiessen, 1960;Cardoso & Veloso, 2003). These clam species also display differences in their size distribution, with smaller individuals settling farther shoreward and larger individuals farther seaward (Matthiessen, 1960;Cardoso & Veloso, 2003).…”
Section: Discussionsupporting
confidence: 70%
“…Postlarval transport of Mya has been noted in other studies. At another site in Massachusetts, Matthiessen (1960) described temporal changes in the spatial distribution of 2-15-mm Mya, which were similar to changes in the distribution of sediments. In Nova Scotia, Canada, Roegner (1996) found that defaunated plots were recolonized by 1-6-mm Mya, similar to the size of Mya found in our study.…”
Section: Discussionmentioning
confidence: 61%
“…However, observations of such spatial patterns on only 1 sampling occasion cannot give conclusive evidence for migration. The following 3 possible processes can also produce a spatially different body size or age composition in a population: (1) locally differential recruitment of different cohorts (Jumars 1978, Thompson 1982, Tamaki 1985; (2) passive transport of individuals in a size-or age-specific fashion by waves and/or currents (Dales 1952, Matthiessen 1960, Gilbert 1968, Brown 1982, Thompson 1982; (3) locally differential growth and/or mortality of individuals (Stephen 1928, Gibbs 1968, Green 81 Hobson 1970, Thompson 1982, Omori et al 1984. Thus, to confirm migration in a population, it is at least necessary to examine temporal change in the spatial distribution of the size (age) classes of the population.…”
Section: Discussionmentioning
confidence: 99%